PUBLIC ACCEPTANCE TOWARDS PARTICIPATION OF DISABLED PEOPLE IN PHYSICAL ACTIVITY - Abdul Rasid Aida Roha; Ong Tah Fatt (Program Pascasarjana Universitas Negeri Jakarta, 2017)
AbstractDesire to be accepted by other people is one of the basic human needs. Social isolation or rejection is very stressful to person with disabilities. Social acceptance by normal people towards physical activity participation for the disabled plays a vital role in motivating them to be more physically active. A review of literature indicated that there are several factors that influence public acceptance towards participation of people with disabilities in physical activity. The present study aims to examine the factors that influence public acceptance towards people with disabilities involvement in physical activity. Based on the Theory of Reasoned Action and Cultural Values Theory, four factors (public attitudes, exposure, ethnicity and subjective norms) were examined in this study. A stratified and convenience sampling technique was adopted to collect data from public without disabilities (N=444), who were exercising at four public recreational parks in Klang Valley, Malaysia. The instrument was developed based on previous study and opinion of a panel of experts. Regression analyses were employed to examine the relationship between the variables. The result showed that the relationship between subjective norms and acceptance has the highest value (R2=0.179), compared to attitude (R2=0.146), ethnicity (R2=0.073) and exposure (R2=0.044). The result indicated that stressing on family supports, mutual contacts and promoting positive attitude of the public are promising approaches to improving public acceptance towards participation of the disabled in physical activity. Emphasizing the related factors can help to reduce the public stigma, which is one of the main obstacles to providing healthy lifestyles for the disabled.Keywords: Attitude; Ethnicity; Exposure; public Acceptance; People with Disabilities; Physical Activity.